# Prove that : (cotx - tanx)/(cotx + tanx) = cosx^2 - sinx^2

Posted on

The identity `(cotx - tanx)/(cotx + tanx) = cos^2x - sin^2x` has to be proved.

`(cotx - tanx)/(cotx + tanx)`

=> `((cosx/sinx) - (sinx/cosx))/((cosx/sinx)+(sinx/cosx))`

=> `((cos^2x - sin^2x)/(sinx*cosx))/((cos^2x + sin^2x)/(sinx*cosx))`

=> `(cos^2x - sin^2x)/1`

=> `cos^2x - sin^2x`

which is the right hand side

This proves that `(cotx - tanx)/(cotx + tanx) = cos^2x - sin^2x`

Posted on

since cotx = cosx/sinx and tanx = sinx/cosx

so (cotx - tanx)/(cotx + tanx)

= (cosx/sinx - sinx/cosx)  / (cosx/sinx + sinx/cosx)

= [(cosx^2 - sinx^2)/sinxcosx]  / [(cosx^2 + sinx^2)/sinxcosx]

= (cosx^2 - sinx^2)/sinxcosx  X   sinxcosx /(cosx^2 + sinx^2)

sinxcosx should cancel each other

and as we know cosx^2 + sinx^2 = 1

so we have

(cosx^2 - sinx^2)/1 X   1/1

=   cosx^2 - sinx^2

Hence  (cotx - tanx)/(cotx + tanx) = cosx^2 - sinx^2 proved

Posted on

since cotx = cosx/sinx and tanx = sinx/cosx

so (cotx - tanx)/(cotx + tanx)

= (cosx/sinx - sinx/cosx)  / (cosx/sinx + sinx/cosx)

= (cosx^2 - sinx^2) /   (cosx^2 + sinx^2)

sinxcosx                      sinxcosx

= (cosx^2 - sinx^2) X   sinxcosx

sinxcosx                    cosx^2 + sinx^2

sinxcosx should cancel each other

and as we know cosx^2 + sinx^2 = 1

so we have

(cosx^2 - sinx^2) X   1

1                   1

=   cosx^2 - sinx^2

Hence  (cotx - tanx)/(cotx + tanx) = cosx^2 - sinx^2 proved

Posted on

L:H:S ≡ (cotx - tanx) ÷ (cotx + tanx)

= [(cos²x-sin²x)/sinx.cosx] ÷ [(cos²x+sin²x)/sinx.cosx]

= (cos²x-sin²x) ÷ (cos²x+sin²x)

we know that sin²θ + cos²θ = 1

= cos²x-sin²x

= R:H:S